Determinants of Dental Referral Practices Among WIC Nutritionists in North Carolina - Elizabeth A. Shick, DDS, MPH; Jessica Y. Lee, DDS, MPH, PhD; R. Gary Rozier, DDS, MPH (Blackwell Synergy, 2005)
To examine the effects of knowledge and confidence on dental referral practices among WIC nutritionists in North Carolina.